Customer Behavior in E-Commerce Purchase from Learning Style - Diaz-Munoz, H (Elsevier B.V., 2022)
This research aims to analyze and interpret the behavior of customers who purchase via e-commerce, initially using traditional marketing tools, and then comparing them with neuromarketing tools such as EEG, VAK tests and Kolb learning styles. It begins with an online survey on e-commerce purchasing preferences, obtaining the classification by gender, socioeconomic group and other classic classifications, adding the VAK and Kolb learning styles as classifiers, both in the perception of an input message (VAK) and in its interpretation within potential internet buyers. It concludes with the promising usage of these new tools as contributions to classic marketing. Learning styles complement traditional marketing and especially online marketing, as they allow to better define the market segments to target. © 2022 The Authors. Published by Elsevier B.V.